Narratology beyond literary criticism : mediality, disciplinarity - Meister, Jan Christoph, 1955-; Kindt, Tom; Schernus, Wilhelm (Narratologia ;, 2005)
This anthology presents the results of the Second International Colloquium of the Narratology Research Group (Hamburg University). It engages in the exploration of approaches that broaden Narratology's realm. The contributions illustrate the transcendence.